Pediatric Reference Intervals for Biochemical Markers: Gaps and Challenges, Recent National Initiatives and Future Perspectives - Tahmasebi, Houman (EJIFCC, 2017)
Reference intervals provide valuable information to medical practitioners in their interpretation of quantitative laboratory test results, and are critical in the assessment of patient health and in clinical decision-making. The reference interval serves as a health-associated benchmark with which to compare an individual test result. While the concept of reference intervals and their utility appear straightforward, the process of establishing accurate and reliable reference intervals is considerably complex and involved. Currently, many pediatric laboratory tests are inappropriately interpreted using reference intervals derived from either adult populations, hospitalized pediatric populations, or from outdated and/or inaccurate technology. Thus, many pediatric reference intervals used in diagnostic laboratories are incomplete and may be inappropriate for clinical use. The use of inappropriate reference intervals impacts clinical decision-making and has potential detrimental effects on the quality of patient healthcare including misdiagnosis, delayed diagnosis, inappropriate treatments, and patient risk. These are critical gaps in pediatric healthcare and it is imperative to update and establish appropriate reference intervals for pediatric populations based on specific age- and sex-stratifications. In the present review, specific issues, challenges and deficiencies in pediatric reference intervals for biochemical markers will be discussed. Early studies using hospitalized patients will be examined, followed by a review of recent national and global initiatives on establishing reference intervals from healthy pediatric population. We will highlight the achievements and milestones of the Canadian CALIPER project, including the establishment of a comprehensive biobank and database which has addressed several of these critical gaps. CALIPER’s mandate is to establish and provide comprehensive, up-to-date pediatric reference intervals to all biochemical markers of pediatric disease. CALIPER has also begun knowledge translation initiatives to disseminate its data via peer-reviewed publication, an online database, and a smartphone application to allow greater access to CALIPER pediatric reference interval data. Finally, limitations, future perspectives and harmonization of pediatric reference intervals to improve pediatric diagnostics in Canada and worldwide will be discussed.